Impact of technology on learning and scholarship, and the new learning paradigm - DE MEYER, Arnoud Cyriel Leo (Institutional Knowledge at Singapore Management University, 2016)
Recently I took on the challenge of teaching a course to Undergraduate students at Singapore Management University. It had been more than 20 years since I had taught any Undergraduates, having spent most of my career at Graduate Business Schools. I did it partially because many of my younger colleagues had told me that teaching had changed tremendously. Deep down I may have felt that I was perhaps a little out of touch with what happened inside and, as I would soon discover, outside our classrooms. I was indeed intrigued by the experience. When I entered the classroom for my first class, I was confronted with a forest of laptops, and most students had as well a smartphone if not a tablet computer on the side. The class I taught was very interactive, and I was often surprised how students would pull up additional material through the internet to complement, if not correct, what I had shared. They had done their homework and watched YouTube videos about some of the cast in the cases I taught. And often they had updated the stories discussed in the case.